The Relationship between Social Interaction and Family Support to the Quality of Life of the Elderly - Saraswasta, I Wayan Gede; Insani, Sahara Nurul (Indonesian Journal of Global Health Research, 2024)
In 2045, it is estimated that the population growth rate will enter the Super Aged Society category with the number of elderly ≥ 21% of the total population. This is a challenge because in general the elderly face weaknesses, limitations and inabilities. One of the things that needs to be considered is the quality of life of the elderly. Objective: To identify the relationship between social interaction and family support on the quality of life of the elderly. Methods: Quantitative research design with a cross-sectional data collection approach. The population in this study is all elderly people aged 60 years and above in Jogjogan Village, Bogor. The sampling technique uses purposive sampling with a sample of 92 people. The research has been carried out from February to June 2024. Data collection was carried out using questionnaires and observations. Data analysis uses a computerized process with a static test, namely the chi-square test. Results: The social interaction of the elderly was in the good category (30.4%), family support in the supportive category (53.3%) and the quality of life of the elderly was in the good category (60.9%). The results of the bivariate test showed a significant relationship between social interaction and quality of life (p-value: 0.00), and the relationship between family support and quality of life (p-value: 0.020). Conclusion: Social interaction and family support provided to the elderly are significantly related to the quality of life of the elderly.